ADJACENCY PAIRS ANALYSIS ON TWO INDONESIAN TALK SHOWS: INI TALK SHOW AND SARAH SECHAN - Rifa, Rahmania Syarifah (2018)
This study investigates adjacency pair types as well as the similarities and differences between Ini Talk Show and Sarah Sechan. Adjacency pair types were analyzed based on the frameworks proposed by Schegloff (2007) and Fasold (2006). Meanwhile, the similarities and differences were analyzed based on the distribution of adjacency pair types, the dispreferred responses, and the topics that are discussed. By employing a descriptive qualitative method, this study examines one episode of each talk show with the same topic which is about "Keakraban Pemain Warkop DKI the Reborn". The findings reveal several main points. First, there are eight types of adjacency pairs found in Sarah Sechan, whereas in Ini Talk Show there are only seven types of adjacency pairs. Second, the question-answer sequence and the announcement-acknowledgment sequence are the two most frequent types found in both of the talk shows. Meanwhile, the least frequent type in both talk shows is an invitation-acceptance/rejection sequence. Third, Ini Talk Show serves more various topics than in Sarah Sechan. However, in Sarah Sechan each topic are discussed deeper than in Ini Talk Show. In brief, the adjacency pairs found in the data reveal that Ini Talk show is a more amusing talk show, whereas Sarah Sechan is a more informative talk show.;---Penelitian ini mengkaji tipe-tipe pasangan sepadan dan persamaan juga perbedaan antara Ini Talk Show dan Sarah Sechan. Pasangan sepadan dianalisa berdasarkan teori dari Schegloff (2007) yang dikombinasikan dengan Fasold (2006). Dengan menggunakan metode deskriptif qualitatif, penelitian ini mengkaji satu episode dari setiap talk show dengan topik mengenai "Keakraban Pemain Warkop DKI the Reborn". Hasil penelitian mengungkapkan beberapa poin penting. Pertama, ada delapan tipe yang ditemukan di Sarah Sechan, sedangkan di Ini Talk show hanya ada tujuh tipe. Kedua, dua tipe dengan frekuensi terbanyak di kedua gelar wicara tersebut adalah pertanyaan-jawaban dan pengumuman-penerimaan. Sedangkan, tipe dengan frekuensi terendah dikedua gelar wicara adalah undangan-penerimaan/penolakan. Ketiga, topik di Ini Talk Show lebih bervariasi dibanding topik di Sarah Sechan. Tetapi, setiap topik di Sarah Sechan didiskusikan lebih dalam dibanding di Ini Talk Show. Singkatnya, pasangan sepadan yang ditemukan di data menunjukkan bahwa Ini Talk Show merupakan gelar wicara yang lebih menghibur, sedangkan Sarah Sechan merupakan gelar wicara yang lebih informatif.